Human Resources Intervention Impact on Badan Pemeriksa Keuangan Auditors' Motivation - Aryanto, Muhammad Reza; Welly, John (The Indonesian Journal of Business Administration, 2013)
Bureaucracy reform that happens in BPK is intended to create high performing government. However, BPK still have issues on HR management system, especially on performance appraisal process or MAKIN. MAKIN in BPK hasn’t been a base for compensation for an employee and hasn’t adopted the best practice. Good organizational performance comes from the auditors’ positive behavior. The behavior can be built by improving motivation, enhancing ability, and conquer environmental obstacle. This research will focus on improving employee motivation and try to apply HR interventions as a solution. The research shows that performance appraisal, coaching and mentoring, management and leadership development, reward system, and career planning and development interventions which have 40.96%, 6.45%, 4.43%, 2.30%, and 1.84% effect on auditors’ motivation. Therefore the solutions’ implementation are policy formulation for performance appraisal process improvements, career development based on performance appraisal, compensation and promotion based on performance appraisal, and improvements for employee participatory in organizational goal setting; develop IT database system for MAKIN; create training for performance appraisal raters; career counseling program; and coaching and mentoring program. Keywords: organizational effectiveness, bureaucracy reform, performance appraisal, motivation